Application of solar power plants as aerator power source for biofloc aquaculture of Makaryo Nyoto Farmers Group - Purnawan, Purnawan; Lestari, Nidia; Bekti, Rokhana Dwi; Kautsar, Valensi; Prabowo, Fajar Yulianto; Utama, Made Andy Wira; Azzahra, Icha; Al Ayyubi, Muhammad (Community Empowerment, 2025)
The agricultural and fisheries sectors in Wukirsari Village remain primary economic drivers. However, traditional fisheries management leads to inconsistent catfish and tilapia harvests and high feed costs, hindering Gapoktan Makaryo Nyoto from maximizing profits. The open-air location of the aquaculture development offers significant potential for utilizing sunlight to generate electricity. This study implements a Solar Power Plant (SPP) as a power source for aerators installed in biofloc ponds. The installation, operation procedures, maintenance, and repair of the SPP were socialized to Gapoktan Makaryo Nyoto members. The installed SPP successfully powered a 100W, 220V aerator, supplying oxygen to three biofloc ponds. Increased oxygen supply is expected to support fish growth. By the end of the program, Gapoktan Makaryo Nyoto members were proficient in operating and utilizing the SPP, leading to improved fish harvests and quality. Additionally, surplus power from the SPP was used for lighting the pond area.